2013
DOI: 10.2500/ajra.2013.27.3854
|View full text |Cite
|
Sign up to set email alerts
|

Adenoidal Hypertrophy and Allergic Rhinitis: Is There an Inverse Relationship?

Abstract: This real-life study shows that large adenoids may be associated with absence of allergy, whereas large turbinates may be associated with small adenoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 56 publications
3
47
0
4
Order By: Relevance
“…In the larynx, a correlation between increased endolaryngeal mucous with positive atopic skin prick testing has been reported as well as an increase in endolaryngeal mucous in two patients exposed to transoral allergen stimulation . There has been little published on nasopharyngeal findings in atopic disease other than in regard to the adenoid pad, as mentioned above . One study demonstrated increased interleukin 4 (IL‐4), number of eosinophils, and decreased neutrophils in biopsies taken of the torus tubarius in atopic patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the larynx, a correlation between increased endolaryngeal mucous with positive atopic skin prick testing has been reported as well as an increase in endolaryngeal mucous in two patients exposed to transoral allergen stimulation . There has been little published on nasopharyngeal findings in atopic disease other than in regard to the adenoid pad, as mentioned above . One study demonstrated increased interleukin 4 (IL‐4), number of eosinophils, and decreased neutrophils in biopsies taken of the torus tubarius in atopic patients .…”
Section: Discussionmentioning
confidence: 99%
“…10 A study comparing skin prick testing to endoscopic findings did not correlate this association, 12 and another study demonstrated poor reliability of endoscopy for findings of mucosal inflammation. 13 In pediatric patients, endoscopic nasal findings predictive of allergic rhinitis included inferior turbinate and middle turbinate contact, whereas turbinate color was not predictive of allergic rhinitis, 14,15 and an inverse relationship between adenoid hypertrophy and allergic disease has been demonstrated in the pediatric population. 12,15 Several studies have demonstrated the elevated prevalence of allergic rhinitis in patients with chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of associated loss of productivity is estimated at between $2–3 billion [5, 6]. Apart from being a ‘nuisance disease’ leading to a significant decrease quality of life [7], AR can be comorbid with other respiratory and non-respiratory disorders such as asthma [8], chronic otitis media [9], rhinosinusitis [10], turbinate hypertrophy [11], secondary obstructive sleep apnea, and sleep difficulties [12]. Evidence suggests that AR often occurs co-morbidly with mood disorders, such as depression [13], and suicidal behaviors [14].…”
Section: Introductionmentioning
confidence: 99%
“…The complete description of the procedure was previously described in detail (7). Briefly, the nasal fossa was evaluated in 3 steps that allowed to investigate the following anatomical structures according to Lang's description (8): i) the inferior turbinate and its relationship with the inferior meatus, the inferior part of the septum, the aspect of the mucosa and the presence of secretion, and the rhinopharynx; ii) the maxillary line (which begins superiorly at the middle turbinate attachment corresponding at the aggernasi area), the olfactory tract when possible, the middle turbinate and its contacts with septum or uncinate process; iii) the uncinate process, the middle meatus and the half posterior of the nasal septum, the ethmoidalis bulla and its mucosal contacts, and the spheno-ethmoidal recess; this step was possible only when the space inside the nasal fossa was adequate, otherwise after local decongestion.…”
Section: Study Proceduresmentioning
confidence: 99%